PENGEMBANGAN MEDIA PEMBELAJARAN “MODUSA” (MONOPOLI BUDAYA NUSANTARA) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN IPS DI SD NEGERI PILANG 3 - Andrea Bremari Ayu Respati; Sulistyo; Endang Surjati (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aimed to develop and examine the effectiveness of Modusa (Monopoli Budaya Nusantara) as a game-based learning medium to improve students’ motivation and learning outcomes in Social Studies learning on the topic of Indonesian cultural diversity in elementary school. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 58 students of SD Negeri Pilang 3 Probolinggo. Data were collected through expert validation sheets, teacher and student response questionnaires, motivation questionnaires, and pre-test and post-test instruments. The findings revealed that Modusa achieved a very high level of validity based on expert evaluations, with an average score of 94.06%, indicating that the developed media was highly feasible for use in Social Studies learning. Teacher and student responses also demonstrated that the media was highly practical and effective, with percentages of 96.5% and 96.12%, respectively. Furthermore, the implementation of Modusa significantly improved students’ learning motivation, which reached 94.53% in the very high category. Students’ learning outcomes also increased, as shown by the improvement in average scores from 65.86 in the pre-test to 88.27 in the post-test, while classical learning mastery increased from 46.55% to 84.48%. The study indicates that integrating educational games with Indonesian cultural content through a Game-Based Learning approach can create a more interactive, contextual, and meaningful learning experience for elementary school students.